PSYCHOSOCIAL FACTORS OF MARRIAGE STABILITY AND LONGEVITY IN TRADITIONAL RWANDA - Mukashema, Immaculée; Hahirwa, Joseph; Hakizamungu, Alexandre (PEOPLE: International Journal of Social Sciences, 2019)
This paper from a research using qualitative approach looks at the marriage stability and lastingness in the traditional Rwanda. It explores the conditions and factors of marriage stability and lastingness that could serve as a lesson to prevent the scourge the couples are currently witnessing including destruction of marriages. Six focus group discussions composed of Rwandan elders were conducted in Kigali City, in Southern and Western Provinces. In traditional Rwanda, marriage was not all about the newly married couple. The two families would instead get involved and play a crucial role in the whole process of forming the new household and in shaping the psychosocial life of the new spouses throughout their marital life. Spouses would have a psychosocial responsibility to sustain family ties established between their two families by striving not to break their marriage. Additionally, some situations would even prompt one of the spouses to "sacrifice" him/herself to the extent of accepting to live in conjugal trouble and stress in order to protect the wellbeing of their children. Because of these two reasons among others, the traditional Rwandan spouses would feel such an exceptional commitment to marriage life; and therefore, they would show mutual respect and patience to each other during their marital life. Such important values are inexistent today. Participants in this study sate that when patience between spouses was exercised, normal relationships would gradually develop. Overall, patience and perseverance were keys to marriage institution’s stability and longevity in traditional Rwanda, what is hard to observe in today’s society. Spouses in contemporary Rwanda can learn a lot from the ones in ancient Rwanda.